Penerapan Pendekatan Kontekstual untuk Meningkatkan Kemampuan Komunikasi Matematik Siswa SMP Bina Harapan Bangsa - Adang Sapari; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2022)
The purpose of the study is to determine the effect of contextual approaches to the mathematical communication skills of junior high school students. The method in this research is quasi-experimental. The study was conducted at Bina Harapan Bangsa Middle School. With class VIII B stated experimental class which amounted to 30 students and class VIII C stated control class which amounted to 30 students. This research is supported by instruments that have been tested, valid and reliable. The instrument was adjusted to four indicators of mathematical communication ability with 5 items in order to get the experimental class and the control class posttest data. Data testing was performed with data processed using the SPSS 22 application for parametric statistical testing. The results of the study concluded that students' mathematical communication skills in the teaching and learning process with the use of contextual approaches were better than students with ordinary learning.